Experiences and needs of family members of perinatal infant deaths: a meta-synthesis - Cui, Nana; Wu, Shasha; Wang, Xiaoyun; Sheng, Lei (Frontiers in Public Health, 2025)
PurposeThis meta-review of qualitative studies aims to explore the experiences and needs of family members following perinatal infant deaths.DesignA qualitative meta-synthesis was conducted.Data sourcesFour databases, PubMed, CINAHL, EMBASE, and Web of Science, were searched from inception through November 2024. An initial search using the keywords “perinatal death”, “family members”, and “qualitative research” retrieved 496 articles. Based on predefined inclusion and exclusion criteria, 10 studies were selected for inclusion.Review methodologyThe Critical Appraisal Skills Programme (CASP) Qualitative Research Checklist was used to assess the quality of included studies.ResultsTen studies from nine countries were analyzed, yielding five overarching themes: negative emotional reactions, searching for the cause of death, rebuilding of life, reconstruction of meaning, and need for support.ConclusionNegative emotional responses are an inevitable and profound part of the bereavement process for families experiencing perinatal loss. Identifying the cause of death helps families understand their loss and reduces uncertainty and self-blame. Central to the grieving process is the reconstruction of emotional and psychological meaning, which involves redefining life's purpose and gradually restoring a sense of normalcy. However, many of these families' needs remain unmet. There is an urgent need for multidisciplinary strategies to provide comprehensive, tailored support.